Gut microbiota and quantitative traits divergence at different altitude of long-tailed dwarf hamsters, Cricetulus longicaudatus - Ren, Yue; Tao, Mengfan; Wang, Xiaoliang; Pu, Xinsheng; Guo, Guangtong; Chen, Kuiyou; Zhao, Bingyu; Hou, Yu; Yang, Xin'gen; Xu, Yumei (Frontiers in Microbiology, 2025)
To investigate the community structure and diversity of gut microflora and their function in body mass regulation, as well as the effects of various locations on gut microbiota and Cricetulus longicaudatus body mass regulation at various elevations. We examined the diversity, abundance, and community structure of the gut microbiota of long-tailed dwarf hamsters from eight regions in Shanxi province during summer using 16S rDNA sequencing technology and analyzed the relationships between these microbiota and environmental variables as well as morphological indicators. The results revealed Firmicutes and Bacteroidetes as the dominant phyla at the phylum level, with Lactobacillus emerging as the predominant genus. We observed differences of gut microflora between different areas, and this diversity is affected by altitude. The high-altitude areas individuals had lower β diversity of gut microbiota than the low-altitude area. Moreover, the body and skull indexes of long-tailed dwarf hamsters also changed with altitude. The result presented in this study indicated that the body size of long-tailed dwarf hamsters conforms to Bergmann's law. And Providencia had significant correlation with body size. Finally, functional analysis of the gut microbiota showed changes in metabolic function that depended on elevation, and collinear network analysis showed how the gut microbiota interacts with each other. All of these results suggest that long-tailed hamsters are different depending on their altitude, with altitude being the main factor affecting both the structure of microbes and the way their metabolism works. This study shows that altitude has a big effect on the gut microbiota and phenotypic traits of long-tailed hamsters. It also shows how well this species can adapt to changes in altitude.